DNMT1 mutations leading to neurodegeneration paradoxically reflect on mitochondrial metabolism. (27th January 2020) - Maresca, Alessandra; Del Dotto, Valentina; Capristo, Mariantonietta; Scimonelli, Emanuela; Tagliavini, Francesca; Morandi, Luca; Tropeano, Concetta Valentina; Caporali, Leonardo; Mohamed, Susan; Roberti, Marina; Scandiffio, Letizia; Zaffagnini, Mirko; et al.
Abstract: ADCA-DN and HSN-IE are rare neurodegenerative syndromes caused by dominant mutations in the replication foci targeting sequence (RFTS) of the DNA methyltransferase 1 ( DNMT1 ) gene. Both phenotypes resemble mitochondrial disorders, and mitochondrial dysfunction was first observed in ADCA-DN. To explore mitochondrial involvement, we studied the effects of DNMT1 mutations in fibroblasts from four ADCA-DN and two HSN-IE patients. We documented impaired activity of purified DNMT1 mutant proteins, which in fibroblasts results in increased DNMT1 amount. We demonstrated that DNMT1 is not localized within mitochondria, but it is associated with the mitochondrial outer membrane. Concordantly, mitochondrial DNA failed to show meaningful CpG methylation. Strikingly, we found activated mitobiogenesis and OXPHOS with significant increase of H2 O2, sharply contrasting with a reduced ATP content. Metabolomics profiling of mutant cells highlighted purine, arginine/urea cycle and glutamate metabolisms as the most consistently altered pathways, similar to primary mitochondrial diseases. The most severe mutations showed activation of energy shortage AMPK-dependent sensing, leading to mTORC1 inhibition. We propose that DNMT1 RFTS mutations deregulate metabolism lowering ATP levels, as a result of increased purine catabolism and urea cycle pathways. This is associated with a paradoxical mitochondrial hyper-function and increased oxidative stress, possibly resulting in neurodegeneration in non-dividing cells.